Photosensitive Rice (Oryza sativa L.) Varieties under Delayed Planting as an Option to Minimize Rice Yield Loss in Flood Affected T. Aman Season - Biswas, A; Ahmed, M M E; Halder, T; Akter, S; Yasmeen, R; Rahman, M S (Bangladesh Rice Journal, 2020)
Photosensitive rice varieties have higher advantages in delayed planting. The present study was undertaken to figure out the degrees of delayed planting and evaluate the performance of six modern Aman rice varieties (BR11, BR22, BR23, BRRI dhan46, BRRI dhan54) against three sets of delayed planting. Each rice variety showed considerable variations for plant height, days to panicle initiation, flowering and maturity. BR22, BR23, and BRRI dhan54 showed a drastic reduction in days to panicle initiation and varied from 65 to 58 days, 69 to 60 days, and 62 to 55 days respectively, while it varied from 76 to 80 days for the control variety BR11. Similarly, days to flowering of BR22 and BRRI dhan54 showed a gradual decrease following different planting time and varied from 92 to 86 days, and 83 to 77 days respectively, while it varied from 109 to 107 days for the control variety BR11. For the above traits, BRRI dhan44 and BRRI dhan46 showed a moderate reduction depending on the three sets of planting time. Grain yield of BR22, BR23 reduced at the third set with a value ranging from 5.8 to 5.0 t/ha, 6.1 to 5.1 t/ha respectively, while BRRI dhan54 showed consistency in grain yield with a range from 5.3 to 5.2 t/ha. In contrast, grain yield of remaining rice varieties ranged between 5.7 to 4.5 t/ha for BRRI dhan46, 6.2 to 3.9 t/ha for BRRI dhan46 while severe reduction for the control variety BR11 with a range from 4.4 to 2.0 t/ha was observed. In conclusion, BRRI dhan54 was found more suitable rice variety in delayed planting compared with other photosensitive rice varieties. In future, BRRI dhan54 could be used as benchmark rice variety in a special rice breeding programme designed for delayed planting. Bangladesh Rice j. 2019, 23(1): 65-72